Relaksasi Tingkat Stres Pasien Bekam Melalui Pendekatan Senam Tawakal - Fauziah (Spiritualita, 2022)
Many literatures, sources, and research prove that cupping therapy is really safe and beneficial for human health, even cupping therapy has been mentioned in the Qur'an and Hadith as the best treatment. However, there are still many cupping patients who feel afraid because they are afraid of seeing blood, there are also those who are afraid of needles (because cupping therapy is identical to needle puncture), what happens to patients who are afraid of stress. The therapist uses relaxation methods through tawakal exercises to reduce or even eliminate the patient's fear of these things. Tawakal gymnastics are movements such as core movements in prayer that aim to foster peace of mind and soul, and avoid negligence that can turn a servant to His Lord towards self-reliance to Allah SWT.One's commitment to religious services is an effective method for reducing depression, stress, and anxiety. The implementation of relaxation treatment for cupping patients at Aswaja Therapy, Kediri city with a tawakal exercise approach was first carried out by providing an understanding to cupping patients about the tawakal exercise to be applied. The therapists gave directions before doing cupping related to the meaning of tawakal, namely surrendering, representing, and surrendering to God after carrying out activities, doing, acting, and behaving. Tawakal exercise is effective for cupping patients who initially Stress, anxiety, fear and tension about cupping have then been reduced